Regulatory intermediaries in content moderation - Kira Beatriz (Internet Policy Review, 2025)
The modern digital public sphere requires effective content moderation systems that balance the interests of states, technology companies, and the public. This article examines how two pieces of legislation establish regulatory intermediaries in an attempt to strike this balance: the EU's Digital Services Act (DSA) with its out-of-court dispute settlement (ODS) bodies, and the proposed Brazilian Bill 2630/2020, which assigns supervisory responsibilities to CGI.br, a multistakeholder body. The analysis reveals that the design of regulatory intermediaries, including preexisting structures like CGI.br, significantly impacts platform governance and user experiences. While the DSA's ODS model offers a framework for independent and user-friendly dispute resolution, the non-binding nature of its decisions limits its effectiveness. Similarly, concerns remain regarding CGI.br's limited financial and human resources, and its legal fragility, which could undermine its ability to fulfil the responsibilities the Bill assigns to it. By examining these models, the article offers insights for creating more effective participative online governance systems. It provides recommendations for the implementation of the DSA and informs ongoing legislative discussions in Brazil.
Keywords: 300; Content moderation; regulatory intermediaries; Digital Services Act; Brazil